Avaliação de traços de personalidade e de funções executivas em usuários de substâncias psicoativas: impactos no funcionamento adaptativo - Oliveira, Aislan José de (2022)
Introduction: The increase in use of psychoactive substances (PS) in recent years is alarming. Currently, the phenomenon of psychoactive substance use is considered a serious public health problem, causing social, economic, individual and health repercussions to users. The literature points to the neuropsychological impacts of the use of PS in important brain areas of users, especially the frontal areas, resulting in changes in the functioning of complex cognitive components such as Executive Functions (EFs). EFs mobilize, recruit, and modulate cognitive components such as attention, memory, impulsivity, and even more intricate cognitive skills such as planning, emotion regulation, and decision making. Therefore, changes in the EFs directly impact the quality of life and the global functioning of users who can have their behavior evaluated as adapted or not adapted in relation to the environment. Objective: To compare the performance of consumers and non-consumers of psychoactive substances in tests that assess personality, impulsivity, executive dysfunctions and executive functions in two independent groups. Methods: This is an quantitative and correlational study, comparing the results of two groups of 80 participants. For the composition of the groups, the ASSIST instrument was used to screen the use of PS. Group one, 1, was composed of PS users undergoing treatment and with scores above 27, which indicate high involvement of use, and the other group was composed of individuals self-declared not dependent on PS and with a maximum score of 3, which indicate low involvement of PS use. The sample was composed of male individuals aged between 18 and 60 years old, regardless of schooling and marital status. Data regarding personality assessment were collected using the NEO-FFI-R instrument, and the assessment of executive functions used the Barratt Impulsiveness Scale - BIS 11, Five Digits Test – FDT, and the Barkley Deficits in Executive Functioning Scale– BDEFS. Results: to compare the results between the groups, the non-parametric Wilcoxon test was used. The study showed that PS users have worse performance (scores) in EFs considering the BDEFS scale in the Organization / problem solving factors, but especially those who receive a load of emotional factors (self-control, motivation, and emotional regulation) the difference was statistically significant (p-value ≤ 0.05). The analysis of the results of the Barratt Scale indicated that the group of users had higher averages in attentional, motor, and non-planning impulsivity, however, with a statistically significant difference for the last two components (p-value ≤ 0.05). The analysis of the NEO-FFI-R instrument indicated that the group of PS users had higher scores in the factors of neuroticism, openness, and conscientiousness, while the group of non-users had higher scores in extroversion and agreeableness, and there was significance in the comparison of the groups in all factors (p-value ≤ 0.05). The analysis of the FTD instrument indicated that the group of users had worse performance in the tasks of reading, counting, choosing, alternating with statistical significance (p-value ≤ 0.05), however this statistical difference was not observed in the calculation of inhibition times and flexibility. Conclusions: The results of this study suggest that users of psychoactive substances present worse performance in the assessment of personality and executive functioning when compared to non-users. It also indicates that the neuropsychological assessment can significantly contribute to the identification of alterations in EFs, serving as an important tool in the identification of therapeutic targets, since the lowering of cognitive functioning compromises the adequate selection of thoughts and behaviors directed to specific goals or objectives such as Commitment to treatment and maintenance of abstinence. Finally, the study points out that personality factors such as emotional instability (neuroticism) and impulsivity can be considered important markers of risk factors for the use of PS, and for strategies to prevent psychopathological conditions such as personality disorders and substance use disorder.(AU)